Sistem Transparansi Keuangan Masjid Al-Furqon Padang - ., Zulfahmi; ., Renita Astri; ., Sularno; Anggraini, Putri; Mulya, Dio Prima; ., Faradika; Putri, Gustiana; Maharani, Aliffa (CV. ITTC INDONESIA, 2024)
The al-furqon mosque, like other mosques, has a cash register for incoming and outgoing money. All financial reports have been prepared properly, but are still written on a blackboard on one of the walls inside the mosque. If the community wants to donate money, they must report and meet directly with the mosque management. In the same way, people should go to the mosque and look at the notes written on the inside walls if they want to know how the mosque's current finances are. because people still have direct physical contact. However, aid continues to flow from the surrounding community and from various sources, such as Padang City and West Sumatra Province.The community service grant proposing team, consisting of lecturers and students from the Information Systems Study Program at Dharma Andalas University (UNIDHA), is trying to help mosque administrators and the surrounding community by using information technology such as the al-furqon mosque website, which provides more complete information about the mosque al-furqon to the general public.